2022
DOI: 10.1111/jdv.17981
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab ocular side effects in patients with atopic dermatitis: a systematic review

Abstract: Atopic dermatitis (AD) is a chronic, inflammatory skin disorder that most frequently occurs in children, but it can also affect adults. Even though most AD cases can be managed with topical treatments, moderate‐to‐severe forms require systemic therapies. Dupilumab is the first human monoclonal antibody approved for the treatment of AD. Its action is through IL‐4 receptor alpha subunit inhibition, thus blocking IL‐4 and IL‐13 signaling pathways. It has been shown to be an effective, well‐tolerated therapy for A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
4
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 77 publications
0
48
4
3
Order By: Relevance
“…Because co-morbid eye symptoms were particularly troublesome for this patient during the spring allergy season, we chose to treat his AD with tralokinumab rather than dupilumab since it may be associated with a lower incidence of conjunctivitis compared with dupilumab. [11][12][13] Tralokinumab (Adtralza ® ) was administered as a subcutaneous injection at an initial dose of 600 mg (four 150 mg injections) followed by 300 mg (two 150 mg injections) administered every other week. Concomitant topical class II corticosteroids and pimecrolimus cream were also applied as required.…”
Section: Case Reportmentioning
confidence: 99%
“…Because co-morbid eye symptoms were particularly troublesome for this patient during the spring allergy season, we chose to treat his AD with tralokinumab rather than dupilumab since it may be associated with a lower incidence of conjunctivitis compared with dupilumab. [11][12][13] Tralokinumab (Adtralza ® ) was administered as a subcutaneous injection at an initial dose of 600 mg (four 150 mg injections) followed by 300 mg (two 150 mg injections) administered every other week. Concomitant topical class II corticosteroids and pimecrolimus cream were also applied as required.…”
Section: Case Reportmentioning
confidence: 99%
“…Interestingly, no cases of new-onset tralokinumab-induced conjunctivitis were observed. Of the two patients who responded well to dupilumab but had severe conjunctivitis [ 20 ], one had no recurrence of conjunctivitis after 16 weeks of tralokinumab, and in the other patient, conjunctivitis persisted but was not aggravated. In both patients, AD remained adequately controlled.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the study by Neagu et al, which provides a concise and comprehensive review of the reported manifestations of dupilumab-induced ocular-surface disease in patients with atopic dermatitis. 1 We have recently conducted a collaborative review involving dermatologists and ophthalmologists on dupilumab-associated ocular side effects (DOSE), in which we presented a management algorithm for the various ocular manifestations. 2 Owing to the controversy surrounding the pathomechanisms behind dupilumab's side effects, our group proposes usage of the term 'dupilumab-associated ocular side effects' to more accurately represent the nature of this entity.…”
Section: Editormentioning
confidence: 99%